2011
DOI: 10.1124/mol.110.068718
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-Dependent Oxidation of Etoposide in Human Myeloid Progenitor CD34+ Cells

Abstract: Etoposide is a widely used anticancer drug successfully used for the treatment of many types of cancer in children and adults. Its use, however, is associated with an increased risk of development of secondary acute myelogenous leukemia involving the mixed-lineage leukemia (MLL) gene (11q23) translocations. Previous studies demonstrated that the phenoxyl radical of etoposide can be produced by action of myeloperoxidase (MPO), an enzyme found in developing myeloid progenitor cells, the likely origin for myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…MPO activity can be efficiently reduced in cell culture systems by the heme biosynthesis inhibitor succinylacetone (SA) (Pinnix et al, 1994; Kagan et al, 2001; Vlasova et al, 2011). By using NB4 cells, an acute promyleocytic leukemia line that express MPO at a high level (Hu et al, 1993), we found that incubation with 200 μ M SA for 48 hours reduced MPO enzymatic activity to below the detection level of the assay employed, and as reported previously (Pinnix et al, 1994), it significantly depleted mature MPO protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPO activity can be efficiently reduced in cell culture systems by the heme biosynthesis inhibitor succinylacetone (SA) (Pinnix et al, 1994; Kagan et al, 2001; Vlasova et al, 2011). By using NB4 cells, an acute promyleocytic leukemia line that express MPO at a high level (Hu et al, 1993), we found that incubation with 200 μ M SA for 48 hours reduced MPO enzymatic activity to below the detection level of the assay employed, and as reported previously (Pinnix et al, 1994), it significantly depleted mature MPO protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Myeloperoxidase is expressed exclusively in cells of the myeloid lineage; it is present at high levels in neutrophils where it exerts its antimicrobial action but is also expressed in myeloid precursor/progenitor cells, including human and mouse common myeloid progenitor and granulocyte/macrophage progenitor cells (Strobl et al, 1993; Mori et al, 2009; Goardon et al, 2011) and is readily detectable in ex vivo normal human bone marrow CD34 + cells (Supplemental Fig. 1) (Strobl et al, 1993; Vlasova et al, 2011). Thus, MPO is likely to be present in the cells in which t-AML arises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that VP-16 metabolites increase Topo II-dependent cleavage near leukemia-associated MLL translocation breakpoints (Lovett et al, 2001). Furthermore, Vlasova et al (2011) have shown that the VP-16 radical formed from 1-electron oxidation can redox cycle, leading to enhanced Topo II-mediated strand breaks and MLL gene translocation. Our previous studies have shown that VP-16 is readily oxidized by × NO chemistry to its phenoxyl radical, an obligatory intermediate in the formation of the VP-16-oquinone (Sinha et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have explored the association of etoposide with acute myeloid leukemia (AML) by using human umbilical cord blood (hUCB) cells (Libura et al, 2005;Vlasova et al, 2011). In the present study, we investigated the effects of mangiferin on the Nrf-ARE signaling pathway and etoposide-induced DNA damage in mononuclear cells (MNCs) from hUCB.…”
Section: Introductionmentioning
confidence: 99%